Rheological Properties of Molten Mixtures of Polypropylene/Copolyamide/Carbon Nanotubes - N. M. Rezanova; M. T. Kartel; Yu. I. Sementsov; G. P. Prikhod’ko; I. A. Melnik; M. V. Tsebrenko (Хімія, фізика та технологія поверхні, 2011)
Effect of carbon nanotubes additives on the rheological properties of polypropylene/copolyamide mixture melts has been investigated. The increase in viscosity and elasticity as well as decrease in the capability of the three-component mixture melts of being longitudinally deformed have been determined. These effects are explained by filling under influence of nanosized additives. It has been shown that the systems with nanosized filler are processed on standard equipments with the use of technological parameters applied to initial mixture.